Artificial Neural Networks - ICANN 2008 - Kurkova-Pohlova, Vera (Springer, 2017)
This two volume set LNCS 5163 and LNCS 5164 constitutes the refereed proceedings of the 18th International Conference on Artificial Neural Networks, ICANN 2008, held in Prague Czech Republic, in September 2008.